Similarity solutions for the boundary layer flow and heat transfer of viscous fluids, nanofluids, porous media, and micropolar fluids - Merkin, John H.; Pop, Ioan, 1937-; Lok, Yian Yian; Grosan, Teodor (Academic Press, an imprint of Elsevier, 2022)
"[P]resents new similarity solutions for fluid mechanics problems including heat transfer of viscous fluids, boundary layer flow, flow in porous media, and nanofluids due to continuous moving surfaces. After discussing several examples of these problems, similarity solutions are derived and then solved using the latest proven methods such as function bvp4c from Matlab, the Keller-box method, singularity methods, and more. Numerical solutions and asymptotic results for limiting cases are discussed in detail to investigate how the flow develops at the leading edge and its end behavior. This book also presents detailed discussions of the mathematical models for boundary layer flow and heat transfer of micropolar fluid and hybrid nanofluid to help readers from a range of disciplinary backgrounds in their research. It also covers the relevant background theory, helping the reader to inform their computational work with a solid understanding of the physical phenomena"--Print version, page 4 of cover.